A SYSTEMATIC REVIEW OF FAMILY CAREGIVERS’ BURDEN HAVING PARENT LIVING WITH MENTAL ILLNESS - RR Dian Tristiana; Ah Yusuf; Rizki Fitryasari; R Endro Sulistyono (UNEJ e-Proceeding, 2023)
Background: Family caregivers play a crucial role in providing care and support for people with mental health conditions, such as schizophrenia. The purpose of this study was to integrate and summarize the current studies of family caregivers’ burden having parents living with mental illness. Method: This systematic review followed Cochrane Collaboration and PRISMA guidelines. Three databases were searched using relevant keywords relating to parents, mental illness, burden, and family members. Three Databases included SCOPUS, Science Direct, and, PubMed. The expanded version of Critical Appraisal Skills Program was used to assess the article quality. Thematic synthesis was conducted on the included papers. Result: Fifteen papers were identified. Most of Family caregivers of parents with mental illness experiences medium to high burden. The study identified 10 sub-themes associated with burden to substitute care. These themes were divided into five themes: Caregiving burden, emotional burden, social alienation, school/work performance difficulties, and economic burden. Conclusion: This review found that additional research is necessary to understand the family caregiver of parent with mental illness experience and how healthcare teams can support them. Further, the findings may help to inform health care policymakers to shift of treatment focus from the patient to the entire household that support family caregivers.